FAKTOR FAKTOR YANG MEMPENGARUH MINAT RUMAH SAKIT ISLAM DI JAWA TIMUR MEMILIH SOFTWARE APLIKASI “SI AISAH” PLJSIAS UMSURABAYA - Anna Marina; Warsidi; Sentot Imam Wahjono; Sabri Balafif; Tri Kurniawati (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2021)
This study aims to determine the interest of Islamic hospitals in East Java in choosing the sharia sofware application “SI AISAH” from the Sharia Accounting Information System Service Centre (PLJSIAS) University of Muhammadiyah Surabaya. This research is a quantitative research using Statistical Package for the Social Sciences Software IBM SPSS version 23. The variables used ini this study are: Sharia, User Safety, Prices, and User Friendly. The population in this study were the leader and employees of Islamic hospital in East Java who were involved with the use of this sofware. Sampling using random sampling tehnique, with a total sample of 105 respondents. The results of the analysis show that the factors that influence the decision of Islamic hospitals in East Java to choose the “SI AISAH” software applicatin from PLJSIAS UMSurabaya are: Sharia (X1), User Safety (X2), Prices (X3), and User Friendly (X4). These four factors influence the decision of Islamic hospitals in East Java in choosing the “SI AISAH” software application only 69,9%, while the remaining 30,1% in influenced by other factor, and the most significants factor is the sharia factor (X1).